TNFSF14: LIGHTing the Way for Effective Cancer Immunotherapy - Skeate, Joseph G.; Otsmaa, Mikk E.; Prins, Ruben; Fernandez, Daniel J.; Da Silva, Diane M.; Kast, W. Martin (Frontiers in Immunology, 2020)
Tumor necrosis factor superfamily member 14 (LIGHT) has been in pre-clinical development for over a decade and shows promise as a modality of enhancing treatment approaches in the field of cancer immunotherapy. To date, LIGHT has been used to combat cancer in multiple tumor models where it can be combined with other immunotherapy modalities to clear established solid tumors as well as treat metastatic events. When LIGHT molecules are delivered to or expressed within tumors they cause significant changes in the tumor microenvironment that are primarily driven through vascular normalization and generation of tertiary lymphoid structures. These changes can synergize with methods that induce or support anti-tumor immune responses, such as checkpoint inhibitors and/or tumor vaccines, to greatly improve immunotherapeutic strategies against cancer. While investigators have utilized multiple vectors to LIGHT-up tumor tissues, there are still improvements needed and components to be found within a human tumor microenvironment that may impede translational efforts. This review addresses the current state of this field.